2014
DOI: 10.1016/j.jksus.2013.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effect of organic and inorganic selenium supplementation on selenium status in camel

Abstract: Selenium deficiency is widely described in livestock from the Arabian Peninsula, notably in the camel, and selenium supplementation is based on cattle or horse requirements, usually with sodium selenite product. In order to test the effect of organic Se supplementation vs inorganic Se, 24 pregnant camels were subjected to 3 treatment groups starting one month before delivery (control without Se, non-organic bolus, organic Se). Blood, milk and feces samples were collected from one month before delivery to 3 mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 41 publications
2
8
0
Order By: Relevance
“…This might be due to the reason that organic Se as a good source of Se, could be utilized by animals in a more effective way, transported and retained in a good order in target tissues or organs compared to the inorganic Se. Similar findings were reported in rams (Berry et al ), buffalo (El‐Siefy ) and boars (Faye et al ; Petrujkic et al ). Moreover, in goats Kumar et al () reported that Zn and Se levels in blood serum and seminal plasma increased significantly ( P > 0.05) at 60, 75, 90 and 105 days as compared to day 0 in the tested group.…”
Section: Discussionsupporting
confidence: 86%
“…This might be due to the reason that organic Se as a good source of Se, could be utilized by animals in a more effective way, transported and retained in a good order in target tissues or organs compared to the inorganic Se. Similar findings were reported in rams (Berry et al ), buffalo (El‐Siefy ) and boars (Faye et al ; Petrujkic et al ). Moreover, in goats Kumar et al () reported that Zn and Se levels in blood serum and seminal plasma increased significantly ( P > 0.05) at 60, 75, 90 and 105 days as compared to day 0 in the tested group.…”
Section: Discussionsupporting
confidence: 86%
“…Milk fat did differ significantly between the groups, although the fourth group was the highest, followed by the third group then the control group and the second group (Table 3). The present result was in agreement with Harrison et al (2005), Wang et al (2009), Faye et al (2014), but the little increment in fat percentage agreed with the results of Silvestre et al (2007) who reported that both monthly fat and protein percent were greater for cows receiving Sel-Plex. Pechová et al (2008) and Liu et al (2008) founded that vitamin E and selenium supplementation increased the concentration and production of milk fat which were significantly higher (p<0.05) in HVE and HSeVE groups.…”
Section: Milk Fatsupporting
confidence: 93%
“…From the literature search provided by the applicant (see above under Section 3.2. Safety) some studies identified are relevant to the ADME of Alkosel ® : namely, one study in laying hens and its effects on performance, eggshell quality and tissue selenium distribution (Invernizzi et al., ) and another in camels (Faye et al., ). These studies confirm SeMet is more easily absorbed, metabolised and retained in tissues than sodium selenite.…”
Section: Assessmentmentioning
confidence: 99%